2015
DOI: 10.7196/sajog.950
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards and knowledge about intrauterine contraceptive devices among women in the reproductive age group in a resource-constrained setting

Abstract: Background. One of the strategies to reduce maternal mortality includes accessible and appropriate contraceptive services to all women. The intrauterine contraceptive device (IUCD) has been identified as a cheap and effective means of contraception by the South African National Department of Health. Objective. To explore knowledge about the IUCD among women using the public health sector and identify any misconceptions. Methods. A sample of 150 women attending antenatal/postnatal clinics were interviewed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…2018; Khatri et al. 2019; Bulto, Zewdie, and Beyen 2014; Dereje, Engida, and Holland 2020; Monji Builu and Naidoo 2015; Khan and Shaikh 2013) and their partners (Shapiro 2016; Gottert et al. 2015; Huber‐Krum et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2018; Khatri et al. 2019; Bulto, Zewdie, and Beyen 2014; Dereje, Engida, and Holland 2020; Monji Builu and Naidoo 2015; Khan and Shaikh 2013) and their partners (Shapiro 2016; Gottert et al. 2015; Huber‐Krum et al.…”
Section: Resultsmentioning
confidence: 99%
“…2020; Robinson et al. 2016; Monji Builu and Naidoo 2015; Van Zijl, Morroni, and Van Der Spuy 2010; Luo et al. 2018; Kathpalia and Mustafa 2015; Khatri et al.…”
Section: Resultsmentioning
confidence: 99%
“…One study conducted in South Africa found the majority of women fear the pain associated with PPIUCD insertion and are concerned that PPIUCD interferes with normal sexual activity. 24 Sunanda and Sudha 25 contend that fear of pain, bleeding, development of cancer and increased body weight deter women from using IUCD. Similarly, these issues were raised as reasons for the nonuse of PPIUCD in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Contraceptive‐related side effects are a major concern among women as reported in this study (reasons for none use of PPICD). One study conducted in South Africa found the majority of women fear the pain associated with PPIUCD insertion and are concerned that PPIUCD interferes with normal sexual activity 24 . Sunanda and Sudha 25 contend that fear of pain, bleeding, development of cancer and increased body weight deter women from using IUCD.…”
Section: Discussionmentioning
confidence: 99%
“… 7 In South Africa, short-acting contraceptives such as condoms, injectables and oral contraception take preference as the choice of contraception among women of childbearing age. 1 , 8 , 9 The Implanon and the copper IUCD are the two forms of LARC that are available in the primary health care (PHC) setting in South Africa.…”
Section: Introductionmentioning
confidence: 99%